2023
DOI: 10.1007/s10853-022-08104-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the laser fluence on the microstructure and the relating magnetic properties of BaFe12O19 films grown on YSZ(111) by PLD for optimized perpendicular recording

Abstract: High-quality BaFe12O19 (BaM) films with high uniaxial anisotropy fields of HA = 17.5 and 18.5 kOe were obtained by pulsed laser deposition (PLD) at two fluences of 1.5 and 5.1 J/cm2 on YSZ(111) substrate, using a platinum interlayer for reducing lattice mismatch. We demonstrated that the microstructure, morphology, and stoichiometry of the hexaferrite BaFe12O19 films can be affected by raising the corresponding energy per pulse from 25 to 75 mJ. However, we also concluded that the increase of fluence leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Hexagonal barium ferrite (BaFe 12 O 19 , BaM) has attracted tremendous attention of several research groups because of their achievements in growing the c -axis perpendicularly oriented BaM thin films with a high anisotropy field H A and with a relatively high perpendicular coercivity Hc ⊥ , which could be usable for high-density perpendicular recording media . Several difficulties were encountered during the growth of BaM films by sputtering, pulsed laser deposition (PLD), , molecular beam epitaxy (MBE), and others. These limitations included chemical intermixing between the BaM layer and the used substrates like SiO 2 , , SiC, MgO, Al 2 O 3 , and YSZ(111) .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hexagonal barium ferrite (BaFe 12 O 19 , BaM) has attracted tremendous attention of several research groups because of their achievements in growing the c -axis perpendicularly oriented BaM thin films with a high anisotropy field H A and with a relatively high perpendicular coercivity Hc ⊥ , which could be usable for high-density perpendicular recording media . Several difficulties were encountered during the growth of BaM films by sputtering, pulsed laser deposition (PLD), , molecular beam epitaxy (MBE), and others. These limitations included chemical intermixing between the BaM layer and the used substrates like SiO 2 , , SiC, MgO, Al 2 O 3 , and YSZ(111) .…”
Section: Introductionmentioning
confidence: 99%
“…Several difficulties were encountered during the growth of BaM films by sputtering, pulsed laser deposition (PLD), , molecular beam epitaxy (MBE), and others. These limitations included chemical intermixing between the BaM layer and the used substrates like SiO 2 , , SiC, MgO, Al 2 O 3 , and YSZ(111) . It was demonstrated that a BaM recording layer with perpendicular easy magnetization was formed on a substrate by means of an underlayer that favors the BaM layer growth with the easy magnetization direction perpendicular to the substrate .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations